Root canal morphology of South Asian Indian maxillary molar teeth - Singh, Shishir; Pawar, Mansing (European Journal of Dentistry, 2015)
Objective: The objective was to study the root canal morphology of South Asian Indian Maxillary molars using a tooth clearing technique. Materials and Methods: Hundred teeth each comprising of first, second, and third molars collected from different dental schools and clinics in India were subjected to standard dye penetration, decalcification and clearing procedure before being studied. Results: The first molar mesiobuccal roots exhibited 69% Type I, 24% Type II, 4% Type IV, 2% Type V, and 1% exhibited a Vertuccis Type VIII canal anatomy. In the group with three separate roots the second molar mesiobuccal roots in exhibited 80.6% Type I, 15.3% Type II, 2.7% Type IV, and 1.4% Type V canal anatomy while the third molars mesiobuccal roots exhibited 57.4% Type I, 32% Type II, 2.1% Type III, 8.5% Type IV, 1% had a Type V canal anatomy in the similar group. Conclusion: A varied root canal anatomy was seen in the mesiobuccal root canal of the maxillary molars.
Keywords: Clearing; India ink; maxillary molars; morphology; root canal; Vertucci